Low-dose ropivacaine for supraclavicular brachial plexus block combined with general anesthesia for successful postoperative analgesia: A case series - Toshio Iwata; Kazuyoshi Nakahashi; Satoki Inoue; Hitoshi Furuya (Saudi Journal of Anaesthesia, 2013)
Background: Ropivacaine, a long-acting local anesthetic agent, has been used for postoperative analgesia in brachial plexus block (BPB) at high doses. However, use of lower doses would reduce the occurrence of adverse effects. Methods: We applied BPB with low-dose ropivacaine (10 mL of 0.375% ropivacaine) after induction of general anesthesia for surgery of the upper extremities in 62 patients at our hospital. Ropivacaine was administered via a fluoroscopy-guided supraclavicular method. Analgesic effects during surgery, visual analog scale pain scores, skin sensation, muscle strength, and postoperative patient satisfaction indices were evaluated. Results: Fifty-six patients (90.3%) did not require supplemental analgesics during surgery. The remaining six patients were administered fentanyl due to the insufficient analgesic effects of the nerve block. Some adverse effects, including numbness and delayed motor and sensory recovery of the upper extremities, were observed. The mean postoperative patient-evaluated visual satisfaction scale was 94.1. Conclusions: Our results suggest that low-dose ropivacaine is clinically acceptable for BPB under general anesthesia.